2020
DOI: 10.3389/fcimb.2020.00135
|View full text |Cite
|
Sign up to set email alerts
|

Marmoset Viral Hepatic Inflammation Induced by Hepatitis C Virus Core Protein via IL-32

Abstract: Common marmosets infected with GB virus-B (GBV-B) chimeras containing hepatitis C virus (HCV) core and envelope proteins (CE1E2p7) developed more severe hepatitis than those infected with HCV envelope proteins (E1E2p7), suggesting that HCV core protein might be involved in the pathogenesis of viral hepatitis. The potential role of HCV core in hepatic inflammation was investigated. Six individual cDNA libraries of liver tissues from HCV CE1E2p7 or E1E2p7 chimera-infected marmosets (three animals per group) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…92 However, IL-32 has been shown to promote HCV hepatic inflammation in two separate studies. 125,149…”
Section: Hivmentioning
confidence: 99%
“…92 However, IL-32 has been shown to promote HCV hepatic inflammation in two separate studies. 125,149…”
Section: Hivmentioning
confidence: 99%
“…Necroptosis is induced by inhibition of the PI3K/Akt expression 30 . Furthermore, p‐Akt, as the upstream of IL‐32, participates in the regulation of numerous diseases 31 . The expression of p‐Akt is upregulated in the liver of ANIT‐induced cholestatic mice 32 .…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, p-Akt, as the upstream of IL-32, participates in the regulation of numerous diseases. 31 The expression of p-Akt is upregulated in the liver of ANIT-induced cholestatic mice. 32 In line with these findings, we observed that both IL-32 and p-Akt expressions were elevated in PLC/PRF/5-ASBT cells under the treatment of bile acids and were positively correlated with the bile acid concentration, while inhibition of p-Akt decreased the expression of IL-32 under bile acid stimulation.…”
Section: Il-32 Inhibited Necroptosis In 1% Lcainduced and Anit-induce...mentioning
confidence: 99%
“…Microarray analysis on immortalized human hepatocytes suggested that the HCV core protein induces inflammatory cytokines through the STAT3 signaling pathway [ 41 ] and extracellular HCV core protein activations of STAT3 in human monocytes, macrophages, and dendritic cells (DCs) were observed to related to an interleukin (IL)-6 pathway [ 22 ]. HCV core protein in a primate model was found to induce hepatic inflammation through stimulated expression of IL-32 via phosphoinositide 3-kinases pathway [ 42 ]. On the other hand, the anti-inflammatory effects by the HCV core protein were also evidenced.…”
Section: P Ro- and Anti-inflammatory Regulations By Hepatit...mentioning
confidence: 99%